The Effect of Financial Literacy and Consumption Patterns on Millennials' Investment Choices in Mataram City - Amri, Syaiful; Siswanto, Topan; Helmida, Baiq Ertin; Wardani, Rosyia (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This research aims to analyze the effect of financial literacy and consumption patterns on the investment choices of the millennial generation in the city of Mataram, both partially and simultaneously. The millennial generation is a productive age group that plays a strategic role in economic development but often faces challenges in financial management and long-term investment planning. The approach used is explanatory associative quantitative with purposive sampling technique on 100 millennial respondents aged 25 to 44 years. Data were collected through a Likert scale-based questionnaire and analyzed using multiple linear regression through SPSS. The results of the data analysis show that all research instruments are valid and reliable, the data is normally distributed, there is no heteroscedasticity, and there is no multicollinearity. Partially, financial literacy and consumption patterns each influence investment choices. Meanwhile, simultaneously, both variables significantly influence millennials' investment choices. These findings underscore the importance of enhancing financial literacy and controlling consumption behavior in shaping rational and sustainable investment habits among the younger generation, particularly in urban areas like Mataram City. Keywords: Financial Literacy; Consumption Patterns; Investment Decisions; Millennial Generation; Mataram City